2015
DOI: 10.14802/jmd.15003
|View full text |Cite
|
Sign up to set email alerts
|

Many Faces of Parkinson’s Disease: Non-Motor Symptoms of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a multi-systemic disorder that is characterized by a combination of motor and non-motor symptoms (NMS). The dopaminergic neurodegeneration of PD is involved in the genesis of NMS, but other conditions and side effects of levodopa are also associated with NMS. NMS can develop at all stage of PD and rapid eyeball movement sleep behavior disorder (RBD), constipation, depression, and olfactory dysfunction are considered prodromal signs of PD. Many NMS related with motor deficits and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 53 publications
3
97
0
2
Order By: Relevance
“…Further analysis of participant PDQ-39 scores showed that 55% of participants improved their scores by five points or more. This is a clinically meaningful increase that is consistent with other studies that have shown that motor and non-motor symptoms have a close relationship, and as one improves the other typically improves [14]. The results support the need for further research on the effects of increased physical functioning and the possibility of permanently incorporating a dedicated exercise routine into the treatment plan of individuals with PD.…”
Section: Discussionsupporting
confidence: 88%
“…Further analysis of participant PDQ-39 scores showed that 55% of participants improved their scores by five points or more. This is a clinically meaningful increase that is consistent with other studies that have shown that motor and non-motor symptoms have a close relationship, and as one improves the other typically improves [14]. The results support the need for further research on the effects of increased physical functioning and the possibility of permanently incorporating a dedicated exercise routine into the treatment plan of individuals with PD.…”
Section: Discussionsupporting
confidence: 88%
“…At each time point, patients' mood and sleep quality were assessed, as these can be affected by PD and influence motor learning and consolidation . Sleep problems were evaluated using item I.7 of the MDS‐UPDRS‐I .…”
Section: Methodsmentioning
confidence: 99%
“…Currently available treatments for Parkinson's disease target the dopaminergic features of the disease but do little to address its nondopaminergic symptoms and fail to treat the underlying neurodegeneration and progressive decline in neurologic function. In addition, nonmotor symptoms of the disease (such as psychosis, sleep behavior disorder, gastrointestinal dysfunction, and cognitive impairment), which can be direct or indirect outcomes of dopaminergic and other neuronal loss, are often resistant to dopamine replacement strategies and may be exacerbated by treatment under some conditions . Furthermore, with prolonged use, currently available treatments are often associated with eventual disabling fluctuations, dyskinesias, and dose‐limiting side effects that decrease their benefits .…”
mentioning
confidence: 99%